PERLINDUNGAN HUKUM KAWASAN HUTAN ADAT DI AMMA TOA KABUPATEN BULUKUMBA PERSPEKTIF SIYASAH DUSTURIYAH - Putri, Sulfiana dwi; Hisbullah; Kahfi, Ashabul (Prodi Hukum Tata Negara (Siyasah Syariyyah) Fakultas Syariah dan Hukum UIN Alauddin Makassar, 2024)
The purpose of this study was to describe the form of legal protection for the Ammatoa Indigenous forest area in Bulukumba Regency from the siyasah dusturiyah perspective, a form of legal protection for the Ammatoa Indigenous forest area in Bulukumba Regency, the impact of forest destruction on the Amma Toa Indigenous forest area community in Bulukumba Regency. The results of this study are, the Government has made rules for customary law communities formed with Regional Regulations regarding the status of existence of indigenous peoples, especially regarding customary forests, a form of protection for Amma Toa's customary forest areas. has existed for a long time. The destructive impact of the Amma Toa customary forest area greatly affected the people, because of the right of the Amma Toa indigenous people to utilize water resources in the Amma Toa customary territory. However, in the siyasa dusturiyah perspective, if it is related to the complexity of the problems studied, namely regarding the legal protection of the Amma Toa customary forest area, it can be concluded that in discussing that forests are gifts and mandates from God Almighty, priceless natural wealth must be grateful for, the existence of forests as a gift is seen as a mandate, therefore the forest must be protected and utilized, as a manifestation of gratitude to God Almighty.